Association between Proximity to Major Roads and Sputum Cell Counts - Julie Wallace; Liesel D’silva; John Brannan; Frederick E Hargreave; Pavlos Kanaroglou; Parameswaran Nair (Canadian Respiratory Journal)
BACKGROUND: Air pollution caused by motor vehicle emissions has been associated with exacerbations of obstructive airway diseases; however, the nature of the resulting bronchitis has not been quantified.